Pengaruh Lingkungan Belajar terhadap Kualitas Pembelajaran Siswa di SD Negeri 0102 Sibuhuan - Irma Sari Daulay; Apriana Hasibuan; Dhuha Hasibuan; Lannur Nukmah; Nurul Hasanah; Sila Sakief Hasibuan; Widya Insani Pasaribu (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to determine the influence of the learning environment on the quality of student learning at SD Negeri 0102 Sibuhuan. The learning environment in this context includes the physical condition of the classroom, supporting facilities, social interactions among school members, and the overall learning atmosphere. The research method used is descriptive quantitative with data collection techniques including questionnaires and observations. The sample consisted of 170 Four, five,sixth-grade students selected through purposive sampling. The results of the study show that the learning environment has a significant impact on the quality of student learning. This is evidenced by higher average learning outcomes among students who study in a more conducive environment. Based on the analysis, it can be concluded that the better the learning environment, the higher the quality of student learning.